THE ROLE OF UNIVERSITY IN THE DEVELOPMENT OF REGIONAL INTERACTIONS SYSTEM: FROM UNIVERSAL SCIENTIFIC-EDUCATIONAL MODEL TO EXPERT-TECHNOLOGICAL MODEL - T. Grabelnykh (Publishing House of the State University of Management, 2017)
The authors prove that in modern conditions the model of university development has changed from universal scientific-educational model to expert-technological model, which reflects the new role of university in constructing regional interactions. The authors argue that the expert-technological model of university development will allow implementing regional strategies of social development on the base of united expert infrastructure in the region, the key role in which will be that of university.